Quantifying and enhancing biodiversity at Irish windfarms. - King, Emma Louise (Trinity College Dublin. School of Natural Sciences. Discipline of Zoology, 2026)
As reliance on wind energy is expanding rapidly to address climate change, it is essential that this transition does not place further pressure on biodiversity. Drawing on a transdisciplinary approach, this thesis provides the first comprehensive study on the impact of wind energy on Ireland's habitats and biodiversity, examining barriers and the potential for industry-led mitigation and enhancement measures. In doing so, it advances scientific understanding and practical decision-making around biodiversity at Irish windfarms. In Chapter 2 I review impacts of wind energy on biodiversity in the scientific literature and compared this with how these impacts are addressed in the planning stages of windfarm development. This analysis highlights gaps in our understanding of windfarm impacts across taxonomic groups, and how this reduces opportunities for mitigation in windfarm planning. Using a modified ecosystem accounting framework, I present in Chapter 3 the first site-scale biodiversity-themed ecosystem accounts, demonstrating their utility in identifying areas of high biodiversity importance on windfarms, alongside areas requiring management to further support biodiversity. Building on this, Chapter 4 describes how I combined several datasets with stakeholder engagement to develop evidence-based biodiversity guidelines tailored to the wind energy industry. This work established a robust, scientific foundation to support the implementation of biodiversity mitigation and enhancement at windfarms. To further examine biodiversity guidelines for wind energy, Chapter 5 examines whether bats, a species group thought to be particularly vulnerable to wind energy, utilise areas in close proximity to turbines. Evaluating bat activity across spatiotemporal scales demonstrated the value of context-dependent guidelines and biodiversity monitoring – which I identified as a critical industry knowledge gap. Collectively, the research described in this thesis underscores the importance of utilising a systems approach to understand the biodiversity surrounding Irish windfarms, including acknowledging the gaps in both research and industry practise. Practically, this thesis presents methodologies for decision-support frameworks to guide the Irish wind energy industry in taking meaningful action for biodiversity. Ultimately, this research challenges the common perspective of wind energy and biodiversity as inherently in conflict, demonstrating that, through evidence-based practice and engaged research, windfarms can operate within an iterative, adaptive management framework that advances both climate change mitigation and biodiversity restoration.
APPROVED
Keywords: Wind energy; Biodiversity; Ecology; Renewable energy